The Intersubjective Type of Religiosity: Theoretical Framework and Methodological Construction for Developing Human Sciences in a Progressive Muslim Perspective - Abdullah, Muhammad Amin (Al-Jami'ah Research Centre, 2020)
An everlasting and perpetual peace in the life of different religious adherents anywhere is the prime purpose of human beings. This article will discuss the methods and approaches of religious education in a contemporary multicultural society. Three approaches to the study of religion: dogmatic, critical, and ethical will be elaborated simultaneously. One cannot rely solely on one approach and neglects the two others without having their implications and consequences in the life of multi-religious society. In addition to the religious and Islamic studies perspectives, I will elaborate the issues based on philosophical concepts, i.e. subjective, objective, and intersubjective, as well. The subjective perspective is commonly based on ‘ulūm al-din, meanwhile the objective one is on social sciences. The combination between the two is called, in this paper, as an intersubjective pattern of religiosity. One of its distinctive features is its sensitivity towards and its ability to accommodate the presence of other communities whose rights are respected and guaranteed.[Kedamaian yang kekal dan abadi bagi semua pemeluk agama yang berbeda di berbagai aspek kehidupannya merupakan tujuan utama dari kemanusiaan. Artikel ini membahas beberapa metode dan pendekatan pendidikan agama pada masyarakat multikultural dewasa ini. Tiga pendekatan dalam pengkajian agama yang dogmatis, kritis dan etis akan dielaborasi secara simultan. Satu pendekatan tidak bisa berdiri sendiri dan menegasikan dua yang lain karena implikasinya dalam kehidupan masyarakat yang multireligius. Selain dalam perspektif keagamaan dan keislaman, artikel ini akan mengelaborasi persoalan di atas dengan pendekatan filosofis: subjektif, objektif, dan intersubjektif. Pendekatan subjektif umumnya didasarkan pada ulūm ad-dīn, sedangkan pendekatan objektif didasarkan pada ilmu-ilmu sosial. Perpaduan antara keduanya, dalam artikel ini, disebut dengan pola keagamaan yang intersubjektif. Salah satu kekhasan pola yang disebut terakhir ini adalah sensitifitasnya terhadap kehadiran kelompok lain dan kemampuannya mengakomodasi kelompok lain tersebut sebagai pemegang hak-hak yang harus pula dijamin dan dihormati.]